CPR high-flame-retardant data cable sheath material and preparation method thereof
By using specific components and processes in the data cable protective, the problem of combustible flame retardant performance and mechanical properties in existing technologies is solved, and the effects of high flame retardant, excellent mechanical properties and low -heat release of low smoke and low heat release are achieved.
Patent Information
- Application Number
- CN202411526779.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-21
AI Technical Summary
While improving flame retardant performance, existing data cable sheaths are difficult to maintain good mechanical and processing performance, and there are problems of low heat release and high smoke yield rates.
The linear low -density polyethylene, ethylene symbol, compatibility agent, inorganic flame retardant, phosphoric flame retardant, antioxidant, coupling agent, ultraviolet absorbent, and ultraviolet absorbent, ultraviolet absorbent, and ultraviolet absorbue are used in dual -peak polyethylene Lubricants and other components are squeezed out of the machine twice through double screw to ensure that the component is uniform and plasticized.
It realizes high flame retardant performance, excellent physical mechanical performance and good low temperature performance, while reducing the production and thermal release of flue gas to meet the CPR combustion standards.
Smart Images

Figure BDA0005109438120000011 
Figure BDA0005109438120000101 
Figure BDA0005109438120000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of low-smoke halogen-free cable materials, and in particular to a sheath material for a CPR highly flame-retardant data cable and a preparation method thereof. Background Art
[0002] Data cable is a cable used to transmit data signals and is widely used in computer networks, intelligent security, data centers, security monitoring systems, etc. With the continuous development of informatization and intelligence, the importance of data cables is also increasing day by day, and with it comes higher technical requirements and environmental protection requirements.
[0003] In the prior art, in order to ensure that the flame retardant performance of the cable meets the standard, inorganic flame retardants are usually added to the components of the sheath material. However, the addition of a large amount of inorganic flame retardants will inevitably lead to a decrease in the fluidity of the system and a deterioration in the physical and mechanical properties of the material. Therefore, how to have good mechanical properties, excellent processing performance, low heat release, low smoke generation rate, non-toxicity, environmental protection and other advantages while meeting high flame retardant performance and passing CPR combustion has become the subject to be studied and solved by the present invention. Summary of the invention
[0004] The purpose of the present invention is to provide a sheath material for a CPR highly flame-retardant data cable and a preparation method thereof.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A sheath material for a CPR highly flame-retardant data cable, the raw materials of which include the following components in parts by weight:
[0007]
[0008] According to a further technical solution, the polyethylene is mixed with bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1, and the melt index of the polyethylene is 0.2 to 20 g / 10 min (190° C., 2.16 kg).
[0009] Compared with ordinary polyethylene, bimodal polyethylene has both processing performance and excellent physical and mechanical properties. The low molecular weight part plays a lubricating role to improve the processing fluidity of cable materials, and the high molecular weight part is used to ensure its physical and mechanical strength. Metallocene linear low-density polyethylene has excellent impact resistance and high strength and high toughness. Metallocene linear low-density polyethylene and bimodal polyethylene are the same type of materials and have good compatibility after blending.
[0010] According to a further technical solution, the vinyl copolymer is formed by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and EPDM rubber in a weight ratio of 1:3:1; the melt index of the vinyl copolymer is 0.2 to 10 g / 10 min (190° C., 2.16 kg).
[0011] The vinyl acetate content in ethylene-vinyl acetate copolymer is 28-33% (mass percentage), which has the characteristics of improving the mechanical properties and flame retardant properties of the product. Ethylene-octene copolymer is a polyolefin elastomer material (POE), which has good tolerance to inorganic fillers, and has excellent physical and mechanical properties and good low-temperature properties due to its narrow molecular weight distribution and short chain branch distribution. It also has excellent heat aging resistance and UV resistance because it contains relatively few tertiary carbon atoms. EPDM rubber has good insulation properties, especially for the product's dielectric constant and dielectric strength, which have obvious improvements.
[0012] According to a further technical solution, the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.5-1.2 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.5-1%.
[0013] According to a further technical solution, the inorganic flame retardant is formed by mixing magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3.
[0014] Magnesium hydroxide and aluminum hydroxide can release crystal water when the material is burned, absorbing a large amount of heat, thereby inhibiting the temperature rise of the polymer, delaying thermal decomposition, and reducing the combustion rate. In addition, the water vapor produced by dehydration can dilute the combustible gas, thereby playing a flame retardant effect.
[0015] According to a further technical solution, the phosphorus-based flame retardant is red phosphorus.
[0016] According to a further technical solution, the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0017] According to a further technical solution, the coupling agent is a silane coupling agent.
[0018] In a further technical solution, the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate.
[0019] According to a further technical solution, the lubricant is formed by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0020] Furthermore, the present invention also discloses a method for preparing a sheath material for a CPR highly flame-retardant data cable, comprising:
[0021] Step 1: Add the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber and lubricant into a mixer and mix them evenly;
[0023] Step 2: Use a twin-screw extruder to extrude and granulate the granulated particles, and then use the twin-screw extruder to extrude and granulate the granulated particles again.
[0024] In the above scheme, in step 2, granulation is performed twice, which can effectively ensure that the inorganic flame retardant is mixed evenly and plasticized sufficiently, so that the material performance is stable and pores are not easily generated.
[0025] According to a further technical solution, in step 1, the mixing temperature of the high-speed mixer is 50-100° C., the mixing time is 60-300 s, and the rotation speed is 400-1200 rpm;
[0026] In step 2, the twin-screw extruder is a feeding extrusion granulation mixing type twin-screw extrusion granulator, and the temperature of the two extrusions is 135-185° C.;
[0027] According to a further technical solution, the inorganic flame retardant is dried in a drying room at 60 to 80° C. for 1 to 4 hours before being added, so that moisture can be discharged and pores are not easily generated.
[0028] The terms “include,” “including,” “have,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The terms used herein generally have the ordinary meanings of each term used in the art, in the context of the present invention, and in the specific context, unless otherwise noted. Certain terms used to describe the present invention will be discussed below or elsewhere in this specification to provide additional guidance to those skilled in the art regarding the description of the present invention.
[0030] The working principle and advantages of the present invention are as follows:
[0031] 1. The polyethylene used in the sheath material of the present invention is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1, and the melt index of the polyethylene is 0.2-20g / 10min (190°C, 2.16kg). Compared with ordinary polyethylene, bimodal polyethylene has better processing performance and excellent physical and mechanical properties. The low molecular weight part plays a lubricating role to improve the processing fluidity of the cable material, and the high molecular weight part is used to ensure its physical and mechanical strength. Metallocene linear low-density polyethylene has excellent impact resistance and the characteristics of high strength and high toughness. Preferably, the melt index of the metallocene linear low-density polyethylene is ≥2g / 10min (190°C, 2.16kg). Metallocene linear low-density polyethylene and bimodal polyethylene are the same type of materials and have good compatibility after blending.
[0032] 2. The vinyl copolymer used in the sheath material of the present invention is mixed with ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1, and the melt index of the vinyl copolymer is 0.2-10g / 10min (190°C, 2.16kg). The vinyl acetate content of the ethylene-vinyl acetate copolymer is 28-33%, which has the characteristics of improving the mechanical properties and flame retardant properties of the product. Ethylene-octene copolymer is a polyolefin elastomer material (POE), which has good tolerance for inorganic fillers, and has a narrow molecular weight distribution and short chain branch distribution, so it has excellent physical and mechanical properties and good low temperature performance; and because it contains relatively few tertiary carbon atoms, it has excellent heat aging resistance and UV resistance. EPDM rubber has good insulation properties, especially for the product The dielectric constant and dielectric strength have obvious improvements.
[0033] 3. The compatibilizer used in the sheath material of the present invention is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.5-1.2 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.5-1%, which is used to enhance the compatibility between the components.
[0034] 4. The inorganic flame retardant used in the sheath material of the present invention is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3. Magnesium hydroxide and aluminum hydroxide can release crystal water when the material is burned, absorb a large amount of heat, thereby inhibiting the temperature rise of the polymer, delaying thermal decomposition, and reducing the combustion rate. In addition, the water vapor generated by dehydration can dilute the combustible gas, thereby achieving a flame retardant effect.
[0035] 5. The lubricant used in the sheath material of the present invention is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1. Silicone masterbatch can improve the fluidity of the resin in the molten state, improve the dispersion of fillers, reduce the energy consumption of extrusion and injection molding, and improve production efficiency; it can also improve the surface smoothness of the cable material, reduce the surface friction coefficient, and improve the wear and scratch resistance. Polyethylene wax improves the processing performance of the cable material by reducing the cohesive force between polymer molecules and the friction between the polymer melt and the processing equipment.
[0036] 6. In the process of the present invention, the polymer and powder are premixed in a high-speed mixer, and the flame retardant needs to be preheated and dried. The use of a twin-screw extruder for granulation twice can effectively ensure the uniformity of various inorganic flame retardants, sufficient plasticization of the polymer, stable material performance and optimal state, and pores are not easy to be generated during the use of the material. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with embodiments:
[0038] The present invention will be described in detail below. After understanding the embodiments of the present invention, any person skilled in the art can make changes and modifications based on the techniques taught by the present invention without departing from the spirit and scope of the present invention.
[0039] The terms used herein are only for describing specific embodiments and are not intended to be limiting of the present invention. Singular forms such as "a", "this", "here", "this" and "the" as used herein also include plural forms.
[0040] Embodiment 1:
[0041] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0042] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0043] 50 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0044] 20 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0045] 250 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0046] 1 part of phosphorus-based flame retardant, wherein the phosphorus-based flame retardant is red phosphorus.
[0047] 3 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0048] 2 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0049] 1 part of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0050] 3 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0051] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material comprises the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for 1 hour before use. Then use a twin-screw extruder for extrusion granulation, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0052] Embodiment 2:
[0053] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0054] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0055] 60 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0056] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0057] 240 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0058] 3 parts of phosphorus flame retardant, wherein the phosphorus flame retardant is red phosphorus.
[0059] 2 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0060] 1.5 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0061] 0.5 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0062] 3 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0063] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0064] Embodiment 3:
[0065] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0066] 30 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0067] 40 parts of a vinyl copolymer, wherein the vinyl copolymer is a mixture of ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0068] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0069] 200 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0070] 5 parts of phosphorus-based flame retardant, wherein the phosphorus-based flame retardant is red phosphorus.
[0071] 1 part of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0072] 3 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0073] 1 part of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0074] 4 parts of lubricant, wherein the lubricant is a mixture of silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0075] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0076] Embodiment 4:
[0077] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0078] 20 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0079] 70 parts of a vinyl copolymer, wherein the vinyl copolymer is a mixture of ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0080] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0081] 180 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0082] 4 parts of phosphorus-based flame retardant, wherein the phosphorus-based flame retardant is red phosphorus.
[0083] 1.5 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0084] 1 part of coupling agent, wherein the coupling agent is a silane coupling agent.
[0085] 0.8 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0086] 4 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0087] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0088] Comparative Example 1:
[0089] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0090] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0091] 60 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0092] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0093] 3 parts of phosphorus flame retardant, wherein the phosphorus flame retardant is red phosphorus.
[0094] 2 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0095] 1.5 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0096] 0.5 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0097] 3 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0098] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0099] Comparative Example 2:
[0100] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0101] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0102] 60 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0103] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0104] 240 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0105] 2 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0106] 1.5 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0107] 0.5 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0108] 3 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0109] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0110] Comparative Example 3:
[0111] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0112] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0113] 60 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0114] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0115] 240 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0116] 3 parts of phosphorus flame retardant, wherein the phosphorus flame retardant is red phosphorus.
[0117] 1.5 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0118] 0.5 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0119] 3 parts of lubricant, wherein the lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:1.
[0120] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0121] Comparative Example 4:
[0122] A sheath material for a CPR highly flame-retardant data cable is made of the following raw materials by weight:
[0123] 10 parts of polyethylene, wherein the polyethylene is a mixture of bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1;
[0124] 60 parts of vinyl copolymer, wherein the vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1;
[0125] 10 parts of a compatibilizer, wherein the compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.8 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.9%;
[0126] 240 parts of an inorganic flame retardant, wherein the inorganic flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:3;
[0127] 3 parts of phosphorus flame retardant, wherein the phosphorus flame retardant is red phosphorus.
[0128] 2 parts of antioxidant, wherein the antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:1.
[0129] 1.5 parts of coupling agent, wherein the coupling agent is a silane coupling agent.
[0130] 0.5 parts of ultraviolet absorber, wherein the ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0131] The preparation scheme of the above-mentioned CPR high flame retardant data cable sheath material includes the following steps: adding the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber, and lubricant to a high-speed mixer and mixing them evenly, the mixing temperature of the high-speed mixer is 50-100°C, the mixing time is 60-300s, the speed is 400-1200rpm, and the flame retardant is dried in a drying room at 60°C for one hour before use. Then use a twin-screw extruder to extrude and granulate, and finally use a twin-screw extruder to extrude and granulate the granulated particles, and the extrusion temperature of the two times is 135-185°C.
[0132] The test data of Examples 1 to 4 are shown in Table 1:
[0133] Table 1
[0134]
[0135]
[0136] The test data of Comparative Examples 1 to 4 are shown in Table 2:
[0137] Table 2
[0138]
[0139] It can be seen from Table 1 that the CPR high flame retardant data cable sheath material of the present invention has high flame retardancy. In Examples 1 to 4, the strength of the CPR high flame retardant data cable sheath material is above 10Mpa, the elongation is above 140%, and it has excellent physical and mechanical properties; the oxygen index is between 30 and 40, the flame retardant property is good, and it passes CPR combustion; at the same time, it also has the advantages of resistance to low temperature of -30°C, low smoke and non-toxicity.
[0140] It can be seen from Table 2 that when a certain component of the CPR high flame retardant data cable sheath material is missing, some properties will be reduced. For example, due to the lack of inorganic flame retardant, the oxygen index of Comparative Example 1 dropped sharply, the CPR combustion failed, and the low-temperature impact embrittlement test at -30°C failed; due to the lack of phosphorus flame retardant, the mechanical properties and oxygen index of Comparative Example 2 dropped sharply; due to the lack of antioxidants and lubricants, the mechanical properties of Comparative Examples 3 and Comparative Examples 4 dropped sharply, and the low-temperature impact embrittlement test at -30°C failed.
[0141] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A CPR highly flame-retardant data cable sheath material, characterized in that: The raw materials include the following components in parts by weight: 10-30 parts of polyethylene; 40-70 parts of vinyl copolymer; Compatibilizer 10~20 parts; 150~250 parts of inorganic flame retardant; 1~5 parts of phosphorus flame retardant; 1~3 parts of antioxidant; 1~3 parts of coupling agent; 0.5~1 part of ultraviolet absorber; 2~5 parts of lubricant.
2. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The polyethylene is mixed by bimodal polyethylene and metallocene linear low-density polyethylene in a weight ratio of 2:1, and the melt index of the polyethylene is 0.2-20 g / 10 min (190° C., 2.16 kg).
3. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The vinyl copolymer is prepared by mixing ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene propylene diene monomer rubber in a weight ratio of 1:3:1, and the melt index of the vinyl copolymer is 0.2-10 g / 10 min (190° C., 2.16 kg).
4. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted ethylene-vinyl acetate copolymer, with a melt index of 0.5-1.2 g / 10 min (190° C., 2.16 kg) and a grafting rate of 0.5-1%.
5. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The inorganic flame retardant is prepared by mixing magnesium hydroxide and aluminum hydroxide in a weight ratio of 1:
3.
6. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The phosphorus-based flame retardant is red phosphorus.
7. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The antioxidant is prepared by mixing antioxidant 1010 and antioxidant DLTP in a weight ratio of 1:
1.
8. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
9. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The ultraviolet absorber is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
10. The sheath material for CPR highly flame-retardant data cable according to claim 1, characterized in that: The lubricant is prepared by mixing silicone masterbatch and polyethylene wax in a weight ratio of 1:
1.
11. A method for preparing a sheath material for a CPR highly flame-retardant data cable, characterized in that: Used to prepare the sheath material for CPR high flame retardant data cable according to any one of claims 1 to 10, the preparation method comprising: Step 1: Add the weighed polyethylene, vinyl copolymer, compatibilizer, inorganic flame retardant, phosphorus flame retardant, antioxidant, coupling agent, ultraviolet absorber and lubricant into a mixer and mix them evenly; Step 2: Use a twin-screw extruder to extrude and granulate the granulated particles, and then use the twin-screw extruder to extrude and granulate the granulated particles again.
12. The method for preparing the sheath material for CPR highly flame-retardant data cable according to claim 11, characterized in that: In step 1, the mixing temperature of the high-speed mixer is 50-100° C., the mixing time is 60-300 s, and the rotation speed is 400-1200 rpm; In step 2, the twin-screw extruder is a feeding extrusion granulation and mixing type twin-screw extrusion granulator, and the temperature of the two extrusions is 135-185° C.; The inorganic flame retardant is dried in a drying room at 60-80° C. for 1-4 hours before being added.